Analysing the adoption of lean production in remanufacturing industry - Anjar Priyono; Fazli Idris (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: This paper aims to analyse the challenges of lean manufacturing implementation in the remanufacturing industry. The research was undertaken in three types of remanufacturing company, torque converter, gearbox, and jet engine remanufacturers. This paper describes the characteristics of remanufacturing companies and compares them with the best practice company adopting lean manufacturing best practice: Toyota Motor Company. Through a comparison of the characteristics of the manufacturing environment, macro, and external condition, the challenges of adopting lean manufacturing are identified. Design/methodology/approach: This study utilised a case study method to analyse qualitative data collected from interviews, observations, and focus group discussions. Although case studies are typically used in inductive research, this study followed a deductive approach. Findings: The analysis demonstrated that remanufacturing companies experience challenges due to contextual differences to the benchmark company. The research found that there are some practices that are embedded in remanufacturing companies, but that the companies do not realise that these are lean manufacturing practices. On the other hand, there are a number of external factors that are beyond the remanufacturers' control that hinder the adoption of lean manufacturing. In addition, the aftermarket business of remanufacturers has resulted in a number of distinctive macro condition characteristics that make the adoption of lean manufacturing more complex. Practical implications: Successfully addressing barriers to lean manufacturing adoption might enhance the performance of remanufacturing process. This is because the business of remanufacturing is not value creation, but capturing value from used products. Originality/value: This paper contributes to existing literature examining lean production in remanufacturing companies. It is novel in the sense that it is the first study examining lean production in the remanufacturing industry from organisational and managerial perspectives.
Keywords: 650; Lean manufacturing; Toyota Production System; remanufacturing industry; aftermarket industry; sustainability